Chapter Migrazione alla ricerca di un'identità in La stagione della migrazione al nord di al-Ṭayyib Ṣāliḥ - La Spisa, Paolo (Studi e saggi, 2021)
The novel by Al-Ṭayib Ṣāliḥ The Season of Migration to the North is a classic of the post-modern Arabic literature. The critical literature of the last century has privileged the post-colonial interpretation. One of the aims of this essay is to reveal the inner reality of the main characters, who are not seen from an external point of view, but within a closer relationship with the reader.